Magnetic properties of SrTiO3/Pr2/3Ca 1/3MnO3 multilayers - Niebieskikwiat, D.; Haberkorn, N.; Guitarra, R.; Guimpel, J.; Haberkorn, Néstor; Guimpel, Julio (IOP Publishing, 2010)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina